Systematic realization of cascadable current-mode filters using current differencing transconductance amplifiers - Tangsrirat, Worapong; Surakampontorn, Wanlop (My University, 2006)
In this paper, a variety of cascadable current-mode filter architectures incorporating current differencing transconductance amplifiers (CDTAs) and grounded passive elements are realized. The proposed filter topologies mainly contain the CDTA-based cascaded filter structure and the current feedback loop, which provides a systematic and structural method for realizing general filtering functions. They are convenient for integration, electronically tunable, easy cascadability, of low sensitivity, simple in structure and easy to design. Design examples and simulation results by PSPICE confirm the usefulness of the proposed approach.
Keywords: Current differencing transconductance amplifier (CDTA); Current-mode filter